Предмет: Алгебра, автор: totty98

Решите, пожалуйста, по действиям) ​

Приложения:

Ответы

Автор ответа: Universalka
1

1)\frac{c-d}{c^{2}+cd }-\frac{c}{d^{2}+cd }=\frac{c-d}{c(c+d)}-\frac{c}{d(d+c)}=\frac{cd-d^{2} -c^{2} }{cd(c+d)}=-\frac{c^{2}-cd+d^{2}}{cd(c+d)}\\\\2)\frac{d^{2} }{c^{3}-cd^{2}}+\frac{1}{c+d}=\frac{d^{2} }{c(c^{2}-d^{2})}+\frac{1}{c+d}=\frac{d^{2} }{c(c-d)(c+d)}+\frac{1}{c+d}=\frac{d^{2}-cd+c^{2}}{c(c-d)(c+d)}

3)-\frac{c^{2}-cd+d^{2}}{cd(c+d)}:\frac{c^{2}-cd+d^{2}}{c(c-d)(c+d)}=-\frac{c^{2}-cd+d^{2}}{cd(c+d)}*\frac{c(c-d)(c+d)}{c^{2}-cd+d^{2}}=-\frac{c-d}{d}=\frac{d-c}{d}

Похожие вопросы